PENDIDIKAN KARAKTER SEBAGAI PILAR UTAMA DALAM MEMBENTUK GENERASI PENERUS BANGSA YANG BERMORAL DAN BERTANGGUNG JAWAB - Liasa, Ida; Sulistiani, Indri; Muliana, Selvia (Jurnal Sultra Elementary School, 2023)
Character education is a very important aspect in forming the next generation of the nation who are not only intellectually intelligent, but also have high morals and a sense of responsibility towards society. This article aims to examine various studies related to character education in the context of basic education in Indonesia, as well as how character education can be implemented effectively to form a responsible and moral young generation. Through this literature review, it is hoped that it can provide a clear picture of the importance of character education in elementary schools as part of efforts to create a better society in the future.